ACTIVITY OF SCAPULAR MUSCLES: COMPARISON OF OPEN AND CLOSED KINETIC CHAIN EXERCISES - Šmite, Daina; Upeniece, Irēna; Runce, Agnese; Gapeyeva, Helena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The function of the shoulder region and cervical spine are regulated by the motor control of the scapula. It is important to selectively activate weak muscles and minimally involve tense muscles to improve scapular motor control. The objective of this study was to compare the activity of scapular muscles and the intramuscular balance during various open and closed kinetic chain exercises. Methods: This study included 20 female sedentary office workers. A surface electromyography was used to analyze the activity of the scapular muscle in the correct exercise starting position and during 6 different exercises. Additionally, the optimal intramuscular balance was examined. Results and conclusions: Open kinetic chain exercises is more suitable than closed kinetic chain exercises for training scapular active stability. Horizontal shoulder abduction with external rotation (scapula retraction and internal rotation) while in the prone position was optimal and could be recommended (as well as its modifications with a resistance band) for training programs to improve scapula active stability.